Regulatory modeling for the enhancement of democratic processes in smart cities: a study based on Crowdlaw - online public participation in lawmaking - Bernardes, Marciele Berger (2021)
The advent of Information and Communication Technologies (ICTs) brought a fast development of urban centers, and a debate emerges on how to use ICTs to enhance the development and quality of life in cities and how to make these more efficient. The object of this paper has as the analyze whether or not the traditional regulatory model, based on a system of sanctioning behavior divergent from the normative prescription by the postulates of digital governance. For the elaboration of this paper, we use the method of deductive approach. This way, along with the prominent literature and the experience of good international practices, we must recognize the need for an “intelligent” regulatory modeling thus being, we presented a contribution to building a new legal paradigm toward the enhancement of democratic processes in smart cities, structured on the postulates of Crowdlaw (collective production of the legislative process). Last, we believe that the contributions arising out of this work may fill some of the gaps existing in terms of legal theory production on the regulatory modeling for participative governance.